2012
DOI: 10.1113/jphysiol.2011.221846
|View full text |Cite
|
Sign up to set email alerts
|

Lobule‐specific membrane excitability of cerebellar Purkinje cells

Abstract: Non-technical summary Cerebellar vermis consists of 10 lobules, and each lobule receives different sensory information. Afferent inputs are integrated in cerebellar Purkinje cells (PCs) which are the sole output of the cerebellar cortex. We show that intrinsic membrane properties are widely different between PCs in the spinocerebellum (lobules III-V) and vestibulocerebellum (lobule X).Abstract Cerebellar Purkinje cells (PCs) are the sole output of the cerebellar cortex and function as key to a variety of learn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
57
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(66 citation statements)
references
References 59 publications
(89 reference statements)
5
57
0
Order By: Relevance
“…This means that between the two studies different subsets of Purkinje cells could in fact have been selected for, based on the cells' physiological properties. Recent work indicates that indeed Purkinje cell intrinsic properties can be different (Kim et al 2012;Snow et al 2014), and these differences are likely related to the specific zonal circuitry that they integrate into (Xiao et al 2014;Zhou et al 2014). Moreover, our observation of relatively regular firing at P30 may in fact coexist with the irregular burst-like activity reported by Lorenzetto et al (2009) in light of recent data from an awake preparation that reported the presence of tonic, bursting, and even quiescent modes of Purkinje cell firing (Cheron et al 2014).…”
Section: Discussionmentioning
confidence: 47%
“…This means that between the two studies different subsets of Purkinje cells could in fact have been selected for, based on the cells' physiological properties. Recent work indicates that indeed Purkinje cell intrinsic properties can be different (Kim et al 2012;Snow et al 2014), and these differences are likely related to the specific zonal circuitry that they integrate into (Xiao et al 2014;Zhou et al 2014). Moreover, our observation of relatively regular firing at P30 may in fact coexist with the irregular burst-like activity reported by Lorenzetto et al (2009) in light of recent data from an awake preparation that reported the presence of tonic, bursting, and even quiescent modes of Purkinje cell firing (Cheron et al 2014).…”
Section: Discussionmentioning
confidence: 47%
“…presence of A-type K + current) membrane properties, leading to lobule X Purkinje cells being less excitable and displaying a greater variety of firing patterns in response to depolarizing current pulses (Fig. 4a, b) 99 .…”
Section: Patterned Physiologymentioning
confidence: 99%
“…Although intensively studied, previous work has focused on the charaterization and possible role of SS pauses, with limited interest in the cerebellar cortical location of the studied PCs (Kim et al 2012;Sugihara and Quy 2007;Wadiche and Jahr 2005;Wang et al 2011;Xiao et al 2014;Zhou et al 2014). In the current study, we systemically correlated the locations of PCs with the occurrence of long pauses and found that these cells are often located close to the exposed brain surface, near the craniotomy.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…PCs that have a similar zebrin "identity," i.e., have a similar expression level of zebrin II (from here on: zebrin), typically receive inputs from the same part of the inferior olive, and project their axons to the same part of the cerebellar nuclei (Apps and Hawkes 2009;Brochu et al 1990;Pijpers et al 2006;Sugihara 2011;Sugihara and Quy 2007;Voogd and Ruigrok 2004), creating functional units, or modules. More recently physiological differences between modules have been described in terms of plasticity (Wadiche and Jahr 2005;Wang et al 2011) and firing dynamics and rates (Kim et al 2012;Xiao et al 2014;Zhou et al 2014). In addition, the cerebellar cortex can also be subdivided in zones on the basis of development and function by borders that run perpendicular to the sagittal bands, i.e., into transverse zones (Ozol et al 1999;Reeber et al 2013).…”
mentioning
confidence: 99%